Lower Gastrointestinal Bleeding - Frisancho Velarde, Oscar (2024)
Lower gastrointestinal bleeding (LGIB) is defined as hemorrhage ocurring at any localization distal to the angle of Treitz. About 10 to 15% of all gastrointestinal bleeding episodes are of this type; the rate increases dramatically (20-30%) with advancing age. LGIB encompasses a wide clinical spectrum ranging from trivial hematochezia to massive hemorrhage with shock. Acute lower gastrointestinal bleeding can drive patients to important hemodynamic changes, so its necessary to define the magnitude of blood loss to practice reposition that will stabilize the patients. We review diagnostic and therapeutic algorithms, focusing on colonoscopy, arteriography and the use of radioactive isotopes; we also consider the use of enteroscopy, double-balloon enteroscopy, capsule endoscopy and surgical indications.